Training for Transformation: Opportunities and Challenges for Health Workforce Sustainability in Developing a Remote Clinical Training Platform - Muller, Jana; Reardon, Cameron; Hanekom, Susan; Bester, Juanita; Coetzee, Francois; Dube, Kopano; du Plessis, Elmarize; Couper, Ian (Frontiers in Public Health, 2021)
Background : In 2018, Stellenbosch University’s Ukwanda Centre for Rural Health led a faculty initiative to expand undergraduate health professions training to a new site, nine hours’ drive from the health sciences campus in the sparsely populated Northern Cape Province of South Africa. This is part of a faculty strategy to extend undergraduate health sciences training into an under-resourced part of the country, where there is no medical school. During 2019, the first year of implementation, four final year medical students undertook a longitudinal integrated clerkship at this site, while final year students from other programmes undertook short five-week rotations, with plans for extending rotations and including more disciplines in 2020. The aim of this study was to understand stakeholder perceptions regarding the development of Upington as a rural clinical training site and how this influenced existing services, workforce sustainability and health professions education. Methods: An iterative thematic analysis of qualitative data collected from 55 participants between January and November 2019 was conducted as part of the case study. A constructivist approach to data collection and analysis was used. Triangulation of data collection and reflexive thematic analysis contributed to the trustworthiness of the data and credibility of the findings. Findings: The perceptions of three key groups of stakeholders are reported 1. Dr Harry Surtie Hospital and Academic Programme Managers; 2. Supervising and non-supervising clinical staff and 3. Students from three undergraduate programs of the Faculty. Five themes emerged regarding the development of the site. The themes include the process of development; the influence on the health service; workforce sustainability, a change in perspective and equipping a future workforce. Discussion: This case study provides data to support the value of establishing a rural clinical training platform in a resource constrained environment. The influence of the expansion initiative on the current workforce speaks to the potential for improved capacity and competence in patient management with an impact on encouraging a rural oriented workforce. The findings may have relevance to other institutions in similar settings. The degree of sustainability of the clinical training initiative is explored using Scheirer’s (2005) framework.